EFFECTIVENESS OF BEHAVIORAL COGNITIVE THERAPY ON ANXIETY IN PATIENTS WITH DIABETES MELLITUS - Mardiana; Mas'ud, Alfian; Najman; Sibulo, Megawati; Artiasari, A.; Irawati (Journal of Islamic Nursing, 2023)
Diabetes mellitus is a chronic disease characterized by high blood glucose levels and disturbances in the metabolism of carbohydrates, fats, and proteins due to insufficient insulin hormone. Anxiety in DM sufferers affects fluctuations in blood glucose which causes unstable blood sugar levels, even though diet, physical exercise, and drug use have been attempted appropriately. DM sufferers have three times the risk of anxiety compared to the general population, diabetes complications can make daily life activities more difficult to carry out, resulting in prolonged sadness. Anxiety in Diabetes Mellitus sufferers affects blood glucose fluctuations which cause unstable blood sugar levels, even though diet, physical exercise and appropriate use of medication have been made. Cognitive behavioral group counseling emphasizes how emotional and behavioral problems can be overcome effectively through cognitive restructuring and shows how irrational beliefs interfere and how they can change inaccurate thoughts with a variety of methods. The purpose of this study was to determine the effectiveness of cognitive behavioral therapy for anxiety in people with diabetes mellitus. Methods To electronic data based Pubmed and Google Scholar with keywords in English and Indonesian, which are published nationally and internationally. This literature study uses The Joanna Briggs Institute guideline is used for assess quality and the Prisma checklist to guide this review. from the search for articles found results that have identified as many as 279 articles with the number of results entered as many as 5 articles. This literature study shows that Cognitive Behavior Therapy for anxiety in patients with diabetes mellitus is effective in reducing anxiety in patients with diabetes mellitus. Keywords: Cognitive Behavior Therapy, Anxiety, Diabetes Mellitus